Intervensi Psikoedukasi Dapat Menurunkan depresi pada Pasien Kanker (Journal of Telenursing (JOTING), 2023)
This study aims to examine the effect of psychoeducational interventions on cancer patients who experience depression. The method used was a systematic literature search from randomized controlled trials conducted from 2 September 2022 to 7 September 2022, using Clinical Key Nursing, Embase, Proquest, and Science Direct databases. The results showed that the psychoeducational intervention in the included studies showed a beneficial effect on cancer patients with depression as assessed before the intervention and after using the Patient Health Questionnaire-8 (PHQ-8), Distress Thermometer, and Hospital Anxiety & Depression Scale (HADS). ). The five articles reviewed obtained statistical data on psychological outcomes, namely depression, from P